A case study on differentiation in the mission and role of higher education institutions in Ireland - Highman, Ludovic Adrian Godefroy (Trinity College (Dublin, Ireland). School of Education, 2015)
Higher education has evolved considerably since the early twentieth century. The concept of a system of higher education only emerged after World War II, with the growing understanding that universities are embedded within a system. Indeed, much has changed since the days when universities would consider themselves as “singular entities with various loose linkages (to knowledge, to academia, to the government, to the nation, to the globe) without any single of these references viewed as clearly dominant” (Teichler, 2008, p.356).
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin